Pengaruh Perilaku Usaha dan Pemasaran terhadap Keputusan Pembelian pada PT Mulya Krida Resik Medan - Irvan Rolyesh Situmorang (Jurnal Manajemen Bisnis Eka Prasetya, 2021)
This study aims to determine the effect of Business Behavior and Marketing on Purchasing Decisions at PT Mulya Krida Resik Medan. The research methodology used is quantitative descriptive method. The type of data used in this study is quantitative data, which is obtained in the form of numbers and numbers. Sources of data in the form of primary data and secondary data. Primary data were obtained from distributing questionnaires, secondary data were obtained from companies, journals and books relating to Business Conduct and Marketing and Purchasing Decisions. The population in this study amounted to 176 customers and the sample in this study amounted to 122 customers. Data analysis uses multiple linear regression analysis methods. There is a positive and significant influence between Business Conduct and Marketing on Purchasing Decisions at PT Mulya Krida Resik.